Organized and curated by Klitsa Antoniou and the Contemporary Visual Art Practices Lab - Antoniou, Klitsa (My University, 2026)
Faculty Art Project initiated, organized and curated by Klitsa Antoniou and the Contemporary Visual Art Practices Lab We can never go back again, that much is certain. The past is still too close to us. An Art Intervention by the Fine Arts Department at Forest Park Hotel Cyprus.